Reclamation Tax Calculation at Revenue Service, Regional Financial and Asset Management (Dppkad) Pariaman City(Perhitungan Pajak Reklamepada Dinas Pendapatan, Pengelola Keuangan Dan Aset Daerah (Dppkad) Kota Pariaman) - Zefriyenni; Yogi Wiyandra; Firna Yenila (Universitas Putra Indonesia YPTK Padang, 2020)
Billboard tax calculations conducted by the Revenue, Financial and Asset Management Agency (DPPKA) Kab. Dharmasraya still uses a manual system so that performance is not optimal. The research conducted aims to optimize the calculation of advertisement tax and provide fast service time for ad users and taxpayers. With this research, it is expected to be able to assist the DPPKA in calculating the advertisement tax effectively and efficiently. The research methods used are field research, library research and laboratories. So that a new system analysis is produced by using tools such as Use Case Diagrams, Sequence Diagrams, Class Diagrams, Activity Diagrams and Deployment Diagrams.